2021
DOI: 10.1002/brb3.2117
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral glucose metabolism in bipolar disorder: A voxel‐based meta‐analysis of positron emission tomography studies

Abstract: Background Previous positron emission tomography studies have reported the changes of cerebral glucose metabolism in bipolar disorder. However, the findings across studies remain controversial, containing differing results. Methods A systematic literature search of the PubMed, Embase, Cochrane Library, and Web of Science databases was conducted. We conducted a voxel‐wide meta‐analysis of cerebral glucose metabolism studies, using the seed‐based mapping approach, in patients with bipolar disorder (BD). Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…This is particularly relevant, given the evidence in favour of an imbalanced cAMP and calcium signalling and glycogen synthesis, with a potential impact on lactate metabolism and the overall cortical activity [99][100][101] . Clinical imaging studies have shown that glucose metabolism is altered in BD 102,103 and our study, in accordance with literature, underlines the contribution of microglia and astrocytes in this process 104,105 . It is important to note that 5 of the patients in our cohort where diabetic, although they were equally distributed between the samples (n = 2 in BD, n= 3 in CT) so the downregulation of insulin pathway genes is therefore probably not the result of this comorbidity.…”
Section: Discussionsupporting
confidence: 92%
“…This is particularly relevant, given the evidence in favour of an imbalanced cAMP and calcium signalling and glycogen synthesis, with a potential impact on lactate metabolism and the overall cortical activity [99][100][101] . Clinical imaging studies have shown that glucose metabolism is altered in BD 102,103 and our study, in accordance with literature, underlines the contribution of microglia and astrocytes in this process 104,105 . It is important to note that 5 of the patients in our cohort where diabetic, although they were equally distributed between the samples (n = 2 in BD, n= 3 in CT) so the downregulation of insulin pathway genes is therefore probably not the result of this comorbidity.…”
Section: Discussionsupporting
confidence: 92%
“…Generation of ATP in mitochondria depends largely on oxidative phosphorylation driven by glucose metabolism. Evidence from magnetic resonance spectroscopy [MRS], positron emission tomography [PET] and blood metabolomics indicate that glucose metabolism is impaired or dysregulated in bipolar disorder [ 14 ].…”
Section: Mechanisms Contributing To Cerebral Energy Dysregulationmentioning
confidence: 99%
“…It contained many large pyramidal cells and was the center for movement control. 14 In patients with bipolar disorder, glucose metabolism in the right precentral gyrus increases and might affect the disease and dysfunction, perhaps with links to emotional and cognitive impairment 15 . One recent study showed that the cortex in the right precentral gyrus in some progressive neurodegenerative disorders was becoming thinner such as amyotrophic lateral sclerosis 16 .…”
Section: Discussionmentioning
confidence: 99%